The Analysis of Clean and Healthy Living Behavior Factors on Wood Furniture Informal Workers - Nanik Kurniyati; Isa Ma'rufi; Wiwien Sugih Utami (Universitas Airlangga, 2023)
Introduction: Clean and Healthy Living Behavior (CHLB) is essential to be applied by the community, especially workers who work in the fields of construction, furniture, and others. Workers sometimes do not pay attention to CHLB, so many diseases and even deaths occur due to a lack of awareness of the importance of CHLB. This study analyzes the factors influencing CHLB in the workplaceon informal wood furniture workers at the Occupational Health Effort (OHE) posts. Methods: This type of research is quantitative with an analytical observational approach. The population was all members of the OHE posts in the Kendit Health Center working area in the Situbondo Regency, totaling 40 people. Results: The results that significantly affected workers' attitudes towards CHLB at work on informal wooden furniture workers were knowledge, attitude, infrastructure, workforce and funding. The attitudes about CHLB can also be the basis (foundation) of changes in CHLB behavior in the workplace on informal workers. The results of the observations showed that there were still many workers who smoked and did not wear PPE at work even though these workers had already known that cigarettes contain chemicals that are harmful to health. The adequate facilities and infrastructure at the OHE posts could improve the behavior of CHLB in the workplace. The findings at OHE posts at the Kendit's working area related to funding showed that all members of OHE posts have agreed on a monthly health fund contribution, but this is still not going well. Conclusion: Therewas an influence of attitude and adequate infrastructure at OHE posts on CHLB in the workplace. However, knowledge, workforce, and funding at OHE posts did not have significant effect on CHLB in the workplace.